A ANALYSIS OF WASTE IN THE WAREHOUSING FLOW PROCESS WITH LEAN WAREHOUSING METHOD AT PT. XYZ - Enny Aryanny; Moch. Yusuf Efendi (Tekmapro, 2024)
PT XYZ is a manufacturing company engaged in furniture such as wardrobes, computer desks, and others. As a place to store finished products, warehousing activities at PT XYZ have not been carried out optimally due to wasteful activities. The purpose of this research is to find out the waste and provide suggestions for improvements to reduce waste in the process of warehousing flow of finished products at PT XYZ. This research uses the Lean Warehousing method which consists of Value Stream Mapping, Process Activity Mapping, Questionnaire, and Fishbone Diagram. The results of this study are that there are 5 attributes of waste that often occur, namely furniture products that are placed on the warehousing floor (Inventory 3), the accumulation of inventory of furniture products in the warehouse is not sold out (inventory 2), a long process of looking for furniture products for order preparation (searching time 1), waiting time for the next process (waiting 4), and looking for empty shelves for product storage (searching time 3), The proposed improvements provided can reduce 9 activities and reduce activity time for 193 minutes. The proposed improvements also increase Process Cycle Efficiency (PCE) by 12.69% from 46.90% to 59.59%.